âQUIDYâ QUICK TIDY, LEMARI PENGERING PAKAIAN MENGGUNAKAN SISTEM KERJA HEATER - Aninditya, Dea Nusa; Sari, Kartika Dwi Ratna; Diinillah, Auliyaa Syara; MaÃ¢Â€Â™arif, Afrizal; Maliki, Rizal (Program Kreativitas Mahasiswa - Karsa Cipta, 2014)
Indonesia is a tropical country that have two seasons, dry and wet. So many problems come in the wet season, one of them is the difficulty to dry up the clothes, for example drying up the uniform for student. By the decreasing temperature and the less sunlight intensity in wet season results on the reduction of water vapor on the wet clothes so it would take longer time to dry the clothes. Beside that, the difficulty to get dry clothes also brings the trouble for the scholars. The excessive activities of the students results on the desirability for students to get everything instantly. The scholars are also willing to get dry clothes quickly and instantly. Knowing that fact, to answer the problems above, an innovation called the Quidy (Quick Tidy) is made. Quidywas made with purpose to provide solutions for the difficulty to get dry clothes in wet seasons. This is to answer the problems faced by the households and scholars. In the making of Quidy, we have some processes, e.g. the selection of tools and materials to build Quidy, the terms used for designing Quidy, the designing process of Quidy, look performance from the design of Quidy and the last, evaluation stage. From the results obtained, we expect that Quidy could be a product that solves the problems in dying the clothes in any season. Because of the simplicity the Quidy offered, it is expectedÂ  thatQuidy will be the answers for the difficulty to dry clothes. Besides, by the presence of Quidy, it is expected that Quidy could benefit every people in the society, both for the high ends, the middles and the lows.Keywords : Quidy, Dryer, Chlothes, Heater